Behring sea arbitration. Case presented on the part of the government of Her Britannic Majesty to the Tribunal of arbitration constituted under article I of the treaty concluded at Washington on the 29th February, 1892, between Her Britannic Majesty and the United States of America. - Great Britain.; Bering Sea Tribunal of Arbitration. (London, Printed for H.M. Stationery off., by Harrison and sons, 1893)
Parliament. Papers by command. C. 6918. Mode of access: Internet.